2023
DOI: 10.1108/emjb-09-2022-0161
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sustainability performance and shareholder value: an international fuzzy-set qualitative comparative analysis

Abstract: PurposeConsidering corporate governance (CG hereinafter) practices' variety across Anglo-American and European countries, this study relies on contingency and complexity theories to investigate the effect of environmental sustainability performance (ESP hereinafter) on shareholder value under various configurations of board of directors (BoD hereinafter), firm and country characteristics.Design/methodology/approachThe author used the Thomson Reuters Environment Pillar Score (ASSET4) and the Total Shareholder R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…For example, [23] and other researchers have found positive relationships between environmental performance and stock prices. Jouber's (2023) [24] findings indicate a positive association between environmental sustainability performance and shareholder value, albeit with differences across AngloAmerican and European economies. Other studies by Al-Tuwaijri et al (2004), Endrikat (2016), and Iatridis (2012) also suggest that environmental performance influences stock price movements positively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, [23] and other researchers have found positive relationships between environmental performance and stock prices. Jouber's (2023) [24] findings indicate a positive association between environmental sustainability performance and shareholder value, albeit with differences across AngloAmerican and European economies. Other studies by Al-Tuwaijri et al (2004), Endrikat (2016), and Iatridis (2012) also suggest that environmental performance influences stock price movements positively.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, research by [23] found that companies with low pollution levels tend to gain additional economic benefits, whereas the opposite is true for highly polluting companies. Habib Jouber, 2023 [24] found a positive association between environmental sustainability performance and shareholder value but he found difference result between Anglo-American and European Economies. This is supported by other studies that yield similar results, indicating that a company's environmental performance influences stock price movements in a positive direction [4], [25], [26].…”
Section: Hypothesis Development 21 Environmental Performance and Shar...mentioning
confidence: 98%
“…It is considered that institutional theory is established as a dynamic component that includes factors that influence the interaction between different actors (Athar et al 2023). It is possible to observe that the relationship between organizational innovation, organi-zational learning, the sustainability innovation performance, and the board directors is based on the behavior that firms assume, the government structure, and the strategies that ensure success in the long-term context in which they operate (Melis and Nawaz 2023;Jouber 2023).…”
Section: Adaptation To the Institutional Environment And Organization...mentioning
confidence: 99%